2001
DOI: 10.1007/s004380000363
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the reverse transsulfuration gene mecB of Acremonium chrysogenum, which encodes a functional cystathionine-γ-lyase

Abstract: In Acremonium chrysogenum, biosynthesis of cysteine for the formation of cephalosporin has been proposed to occur through the reverse transsulfuration pathway. A gene, named mecB, has been cloned from an A. chrysogenum C10 genomic library in lambdaEMBL3-ble. The cloned DNA fragment encodes a protein of 423 amino acids with a deduced molecular mass of 45 kDa that shows great similarity to cystathionine-gamma-lyases from Saccharomyces cerevisiae and other eukaryotic organisms. The protein was shown to be functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…These results indicated that those transformants that suffered the canonical recombination process lost the mecB gene in the gene replacement process. These results confirmed that there is a single copy of the mecB gene in A. chrysogenum, as was proposed before on the basis of Southern hybridization evidence (19).…”
Section: Vol 183 2001supporting
confidence: 91%
See 3 more Smart Citations
“…These results indicated that those transformants that suffered the canonical recombination process lost the mecB gene in the gene replacement process. These results confirmed that there is a single copy of the mecB gene in A. chrysogenum, as was proposed before on the basis of Southern hybridization evidence (19).…”
Section: Vol 183 2001supporting
confidence: 91%
“…However, this mutant might have contained a second mutation affecting cephalosporin production and, unfortunately, the CIBA-Geigy mutant is not available for further studies (J. Heim, personal communication). In this article, we have inactivated the mecB gene, which encodes cystathionine-␥-lyase activity in A. chrysogenum (19). The in- activation of the mecB gene does not affect cephalosporin biosynthesis when the sulfur source is sulfate, i.e., cysteine for cephalosporin biosynthesis may be synthesized from either sulfate or methionine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some bacterial species, including B. subtilis, can also synthesize Cys by the reverse trans-sulfuration pathway using Met as a precursor (71,86). The two genes involved in these reactions are yrhA (encoding cystathionine ␤-synthase) and yrhB (encoding cystathionine ␥-lyase), which are commonly found in the same transcriptional unit.…”
Section: Pathways For Synthesis Of the Sulfur-containing Amino Acids mentioning
confidence: 99%